Changes in Cardiovascular Status and Serum Electrolyte Levels During Percutaneous Nephrolithotomy (Bangladesh Journal of Urology, 2020)
Background: Due to advancement of endourology, percutaneous nephrolithotomy (PCNL) is a common procedure for removal of renal stones. Intravascular absorption of normal saline during the PCNL may result in fluid overload, electrolyte imbalance and cardiovascular instability.Objective: To evaluate the changes in cardiovascular status and serum electrolyte levels in patients undergoing percutaneous nephrolithotomy. Method: Sixty adults underwent percutaneous nephrolithotomy were studied. Among them male female ratio was 13:7 and age ranging from 20-50 years. Heart rate, blood pressure and serum electrolytes were monitored before irrigation, during irrigation and post operatively. Stone size, duration of irrigation, volumes of irrigation fluid used and amount of absorption of irrigation fluid were recorded.Result: The mean heart rate, systolic and diastolic blood pressure levels were significantly higher (p